Improving Transient Stability in Power Systems by Using Fuzzy Logic Controlled SVC - Reaza Ashrafi Habib Abadi; Amir Nekoubin (Institute of Advanced Engineering and Science, 2017)
This paper presents the capability of a fuzzy logic based stabilizer used for generating the supplementary control signal to voltage regulator of static VAR compensator (SVC) for improving damping oscillations in power systems. Generator speed deviation and line active power were chosen as input signals for the fuzzy logic controller (FLC). The quantity of reactive power supplied/absorbed by SVC is determined based on the two input signal and deviation of terminal voltage at each sampling time. The effectiveness and feasibility of the proposed control is demonstrated with Single Machine Infinite Bus (SMIB) system and multi machine system which show improvement over the use of a fixed parameter controller. It has been observed that a robust controller is obtained with fuzzy logic controller.